Psychometric properties of the Persian version of postpartum distress measure scale - Shokuhi, Zahra Bakht (BMC Psychiatry, 2020)
BACKGROUND: The purpose of the present study was to determine psychometric properties of the Persian version of Postpartum Distress Measure Scale (PDM Scale). METHODS: In this psychometric explorative study, the data were collected using a questionnaire containing demographic information, PDM Scale, and Depression and Anxiety Stress Scale-21 (DASS-21). The content, face and construct validity of the questionnaire was examined with participation of ten experts, 10 and 150 women referring to health care centers, who were under common care during their postpartum period, respectively. The concurrent validity of the tool was evaluated using DASS-21. The reliability of the items was evaluated with the participation of 30 women, calculating Cronbach’s alpha coefficient and intra-class correlation coefficient. RESULTS: The Content Validity Index, Content Validity Ratio and Impact Score of the Persian version of the PDM were 0.94, 0.73, and 2.97, respectively. The ten items of the questionnaire were loaded in two factors (general distress and obsessive compulsive symptoms subscale). Those two factors explained 50.78% of the total variance of women’s distress. Internal consistency of the items and stability of the results were confirmed by Cronbach’s alpha of 0.72 and Intra-class correlation coefficient of 0.75. CONCLUSION: According to the study results, the Persian version of PDM Scale has acceptable psychometric properties. Care providers and researchers can use it as a tool for screening anxiety, depression and obsessive-compulsive disorder in women.